Revisiting Medieval Philosophers and their Writing: Lessons when Ideas Can Be Dangerous - Susan S., Nash, (IJRDO - Journal of Social Science and Humanities Research, 2018)
In medieval times, the term, “philosophy” encompassed not just the Greek and Roman classics that we consider to be philosophical texts (Aristotle’s Nicomachean Ethics and Categories, for example), but also what we would now consider to be theology, economics, and political science. This made philosophy both more immediately practical and more potentially treacherous, since it could be looked at as destabilizing to vested interests, namely the church and the state (aka, monarchy), which were often intertwined and interdependent. So, philosophy was considered to be of powerful, tangible import, and not simply a bundle of abstract ruminations written in highly specialized language (or jargon), which is the way it is often considered in the 21st century. During the Middle Ages and even through the Renaissance, philosophical texts were living, breathing guides for living. They often illustrated the ideal world or social order (translations of Plato’s The Republic) and the medieval cosmogenies that placed the Earth in the middle of the solar system, were not simply works of speculative astronomy, but also commentaries and guides to notions of earthly hierarchy. God and God’s emissaries, the Kings, were at the center, and the Sun rotated around the Earth, signifying their core importance and the place on the top of the hierarchy and the Great Chain of Being. The texts that were studied during medieval times had often contradictory messages. For that reason, they were used as tools both to reinforce the social order, but also to break away and undermine the dominant institutions, such as the church and the state. To revisit the works and re-examine them from the perspective of rapid social change, and an increasing awareness of how words and ideas can be perceived as destabilizing or nullified as “fake” makes the insights of the medieval thinkers even more valuable.